Intergenerational transfers and wealth in the Euro-area: The relevance of inheritances and gifts in absolute and relative terms - Anita Tiefensee; Christian Westermeier (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
Private wealth is a crucial factor for the economic well-being of households. Key determinants of private wealth include intergenerational wealth transfers (gifts and inheritances), which are gaining importance since 1990, as research suggests. We conduct a detailed investigation of the distribution of wealth transfers in eight Euro-area countries. First, we investigate the patterns of prevalence and level of past wealth transfers in the individual countries: Who received transfers, and what is their present value in absolute terms? We find that in most countries the percentages of households with a transfer as well as the mean present value of those transfers is increasing along the distribution of net wealth. Using a series of country-specific multivariate regressions, we find that households with higher income and education levels have both a higher probability of receiving transfers and higher absolute transfer value. We then analyze the present value of transfers as a percent of current net worth. Here, in relative terms, some of the results are reversed, as the relative importance of intergenerational transfers does not increase with the level of wealth or income. Using a fractional logit regression we conclude that for higher income quintiles the share of current net worth due to past intergenerational transfers tends to be decreasing.
Keywords: D64; D31; D14; 330; intergenerational transfers; inheritances and gifts; wealth distribution